BIOCOMPATIBILITY OF MEDICAL DEVICES - LEGAL REGULATIONS IN THE EUROPEAN UNION. - Mariela Yaneva-Deliverska; Jordan Deliversky; Maya Lyapina (Peytchinski Publishing, 2015)
A multiplicity of laws, standards, and recommendations regulate the marketing of medical devices. Therefore, legal regulations do not release the specialists in the fields of medicine and dentistry from the responsibility to gather as much information as possible about the products used or to request this information from the manufacturer. Safety data sheets for medical devices can be downloaded from the Internet. They are an important source of information about the biocompatibility of dental materials as they were investigated by the manufacturers. Appropriate safety labels on the wrappings should be considered. The manufacturer/importer is responsible for its products and is potentially liable for damages. The medical doctors and dentists should use only those medical devices for which appropriate information is available.